Introduction to the modelling of marine ecosystems - Fennel, W. (Wolfgang); Neumann, T. (Thomas) (Elsevier oceanography series., 2014)
Introduction to the Modelling of Marine Ecosystems, Second Edition provides foundational information on the construction of chemical and biological models - from simple cases to more complex biogeochemical models and life cycle resolving model components. This step-by-step approach to increasing the complexity of the models allows readers to explore the theoretical framework and become familiar with the models even when they have limited experience in mathematical modeling. Introduction to the Modelling of Marine Ecosystems shows how biological model components can be integrated into three dim.